APPLICATION OF THE WAY MODELING METHOD TO IMPROVE STUDENTS 'SPEAKING SKILLS IN CLASS V SDN 4 BULANGO TIMUR - SUMARNI MOHAMMAD; TITA SARI LASABUDA (International Journal of Innovations in Engineering Research and Technology, 2021)
The problem studied in this research is "Can the application of the modeling method the Way improve the speaking skills of students in class V SDN 4 Bulango Timur?" The purpose of this study was to improve students' speaking skills through the application of the Modeling the Way method in class V SDN 4 Bulango Timur. The research method used is classroom action research (PTK). Data collection techniques through observation, tests, and documentation. In the initial observation, 7 students or 36% of the 19 students spoke fluently. In the first cycle after using The Way modeling method increased to 12 people or by (63%). In the second cycle, it increased again to 18 students or (94%) from 19 total students. Based on these results, it can be concluded that the Modeling the Way method can improve the speaking skills of students in class V SDN 4 Bulango Timur.